Free speech handbook : a practical framework for understanding our free speech protections - Rosenberg, Ian (World citizen comics., 2021)
"In this volume of the World Citizen Comics series, Ian Rosenberg and Mike Cavallaro create a practical framework for appreciating where our free speech protections have come from and how they may develop in the future. Freedom of speech is fiercely defended in America and has been since the First Amendment was written. But how does it work, and what laws shape it? Drawing on parallels between ten seminal Supreme Court cases and current events, Free Speech Handbook lays out the fundamentals of First Amendment law in an accessible and engaging way."-- Amazon.com